Phenomenological-hermeneutical approach to borderline personality disorder - Pacheco, Cristóbal; Fossa, Pablo (Emerald Publishing Limited, 2025)
Phenomenological-Hermeneutical Approach to Borderline Personality Disorder explores the subjective experience of individuals living with borderline personality disorder (BPD) through phenomenological and hermeneutic lenses. This volume bridges the gap between psychological theory and lived experience, offering a nuanced perspective on emotional instability, relational disturbances, and the profound existential challenges faced by individuals with BPD. By incorporating methods such as Interpretative Phenomenological Analysis (IPA) and micro-phenomenology, the authors propose a comprehensive framework to uncover the complex inner dynamics of this condition. Dr. Cristóbal Pacheco and Dr. Pablo Fossa approach BPD from multiple perspectives, examining the instability at the core of the condition, the temporal and spatial structures of emotional turbulence, and the centrality of empathy in grasping subjective realities. The text also explores hermeneutics as a means to interpret and reveal deeper layers of meaning, encouraging readers to understand BPD not merely as a diagnosis, but as a complex and multifaceted human experience. This book is an essential resource for psychologists, clinicians, researchers, and students seeking a deeper understanding of BPD, as well as for those interested in phenomenological and hermeneutic approaches. It challenges conventional paradigms by centering the lived experiences of individuals and advocates for a more compassionate and holistic approach to psychological care.
Includes index.
Keywords: Borderline personality disorder.; Psychology -- Psychopathology -- Personality Disorders.; Psychology: the self, ego, identity, personality.; Abnormal psychology.; elektronické knihy; electronic books